Internet Book Publishing -- A Case Study - Nash, John C.; Nash, Mary M. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
This paper presents the history and analysis of the publishing of the book "Scientific Computing with PCs" via the Internet. We detail some of the obstacles to such endeavours and to the analysis of log files of user actions. Recommendations and opinions are offered to those considering Internet publishing ventures.